Clustering Research on Islamic Empowerment Model using R - Uula, Mimma Maripatul; Sanrego, Yulizar Djamaluddin (The Economic Review of Pesantren, 2023)
This bibliometric research was conducted to provide a more in-depth picture of the "Islamic Empowerment Model" by analyzing a number of relevant articles that have been published in the Dimensions database. A total of 233 imlia publication documents in the period 2022-2023 became the object of this research. Using bibliometric analysis methods with the help of Biblioshiny-R software, this study seeks to reveal publication trends over time, identify the most prolific authors in this field, explore journals that have a significant impact in related literature, and reveal the main themes that consistently appear in these scientific works. The results show that the number of publications has increased significantly since 2016, reaching a maximum of 52 publications in 2021 and 2022. 2011 was the year with the highest average number of citations throughout the observation period. The Journal of Social Science Research, is the top publishing journal. There are several authors associated with this journal, such as Huda N, Alhifni A, and Ahwarumi B. The next important finding is that there are 3 research clusters including, Islamic empowerment models through Islamic financial instruments, women's empowerment models in Islam, and Islamic empowerment models through pesantren education. The results of this study are expected to provide valuable insights for various parties, including researchers who want to better understand the development of Islamic empowerment literature, practitioners involved in this field, and academics who want to explore this topic in more depth.